Городской некрополь Судак-II на посаде средневековой Сугдеи - Майко, В.В. (Материалы по археологии, истории и этнографии Таврии, 2006)
Одним из важных источников по истории Крымского средневековья являются плитовые некрополи. Они являются наиболее характерной особенностью христианского погребального обряда на полуострове. Одним из районов наибольшего сосредоточения плитовых могильников в юго-восточном Крыму считается Судакская долина. Тут в разные годы раскопано целиком или частично 27 различных ло величине некрополей, так или иначе связанных со средневековой Сугдеей. In the article the city necropolis of medieval Sudak, Sudak-ll, which was research in 1964-66 by M. A. Frondgylo, and in 1982 by I. A. Baranov has been analyzed for the first time. The analysis of grave goods, construction of burials and their location on the necropolis, enable us to distinguish several chronological groups of burials. They allow to trace the necropolis dynamics of functioning and give the unique objective information about existence of medieval Sudak during each of its periods. It is a really urgent problem especially for the period of the 11th - the first half of the 13th centuries which has been insufficiently researched on the territory of the medieval city.